Factors influencing the durability of the glucose‐lowering effect of sitagliptin combined with a sulfonylurea. Issue 4 (11th February 2014) - Kubota, Akira; Yabe, Daisuke; Kanamori, Akira; Kuroe, Akira; Takahashi, Nobuo; Saito, Tatsuhiko; Matsuba, Ikuro; Nabe, Koichiro; Kurose, Takeshi; Seino, Yutaka
Abstract We analyzed the changes of glycemic control over 12 months and the factors influencing blood glucose in 162 Japanese patients with type 2 diabetes having inadequate glycemic control despite sulfonylurea‐based therapy who received add‐on sitagliptin. Hemoglobin A1c (HbA1c) decreased significantly after 4 weeks of treatment, and this improvement was maintained for 1 year, although HbA1c was slightly higher in week 52 than in week 24. Comparison of the patients showing a ≥0.4% increase of HbA1c between weeks 24 and 52 (n = 57) with the others (n = 105) showed a significant difference in the change of bodyweight, as well as the dose of glibenclamide (both P < 0.01). Although combined therapy with sitagliptin and a sulfonylurea seems to be effective for at least 1 year, blood glucose levels are more likely to increase again in patients who show greater weight gain after 24 weeks of treatment and those receiving a higher dose of glibenclamide.